2013
DOI: 10.1017/s1092852913000102
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the evidence for the treatment of acute depression in bipolar I disorder

Abstract: In this article we examined evidence for the acute treatment of depression in bipolar I disorder, focusing on double-blind, placebo-controlled studies with a definite primary outcome measure and published in peer review journals. Quetiapine and olanzapine/fluoxetine are currently approved by the FDA for the treatment of bipolar depression and a number of additional agents (including other atypical antipsychotics, mood stabilizers, antidepressants, and novel compounds) have been studied with varying degrees of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 55 publications
(209 reference statements)
1
30
0
Order By: Relevance
“…When the retrospective cohorts in the PREVAIL 3 and 1 studies were compared directly, the effect sizes were comparable (0.31 vs. 0.34), and both were lower than the effect size (0.51) observed in the monotherapy trial. This is consistent with previous studies that have shown that adjunctive trials in bipolar depression yield effect sizes that are smaller than those observed in monotherapy trials . Since lithium or valproate monotherapy has some antidepressant effects in its own right, adjunctive use of these agents may enhance placebo response and reduce effect size .…”
Section: Bipolar Depression: Efficacysupporting
confidence: 91%
See 1 more Smart Citation
“…When the retrospective cohorts in the PREVAIL 3 and 1 studies were compared directly, the effect sizes were comparable (0.31 vs. 0.34), and both were lower than the effect size (0.51) observed in the monotherapy trial. This is consistent with previous studies that have shown that adjunctive trials in bipolar depression yield effect sizes that are smaller than those observed in monotherapy trials . Since lithium or valproate monotherapy has some antidepressant effects in its own right, adjunctive use of these agents may enhance placebo response and reduce effect size .…”
Section: Bipolar Depression: Efficacysupporting
confidence: 91%
“…Antidepressants typically are coadministered with a mood stabilizer or an antipsychotic agent. Before the development of lurasidone, two atypical antipsychotic agents had been approved as monotherapies for acute bipolar depression in the United States—olanzapine–fluoxetine combination (OFC; 2003) and quetiapine (2006)—while two other agents (aripiprazole and ziprasidone) had failed to demonstrate efficacy . The results of one previous placebo‐controlled trial examining adjunctive therapy with ziprasidone were negative …”
Section: Treatment Of Bipolar Depression: An Unmet Needmentioning
confidence: 99%
“…Never-the-less, it is recognised by all healthcare professionals that the different AAPs have different mechanisms of action and different effectiveness and safety profiles in patients with major mental illness including BPD (1,(11)(12)(13)(14). Consequently, the choice of AAP prescribed should be tailored to the individual, especially as there are concerns with the effectiveness of some of the current AAPs for the management of depressive phases of bipolar disorders (10,13).…”
Section: Main Textmentioning
confidence: 99%
“…16 Lower treatment effect sizes are notably more frequent in adjunctive therapy studies compared to monotherapy studies. 30 Lithium and valproate each has been shown to have antidepressant effects in some patients with bipolar depression, 31 and a systematic review 32 of older adults with refractory unipolar depression suggests that augmentation with lithium is associated with an increased antidepressant response. In the current older adult analyses, response rates in the placebo group were higher with adjunctive therapy compared to monotherapy (37.0% vs 14.8%), consistent with a contribution of adjunctive lithium and valproate to placebo group response.…”
mentioning
confidence: 99%